HUBUNGAN PENGETAHUAN DAN POLA KOMUNIKASI ORANG TUA TERHADAP PERKEMBANGAN BAHASA PADA ANAK USIA TODDLER DI PUSKESMAS SIDOMULYO PEKANBARU - Mutiara Rizky; Swastika Sekar Utami (Ensiklopedia of Journal, 2026)
Knowledge and communication are important aspects of child growth and development, particularly during the toddler period, which is a critical stage for language acquisition and development. This study aimed to determine the relationship between parental knowledge and communication patterns and language development among toddlers at Sidomulyo Community Health Center (Puskesmas Sidomulyo). This research employed a quantitative approach with a cross-sectional study design. The study was conducted at Sidomulyo Community Health Center from July 21 to July 31, 2025. A purposive sampling technique was used to select 86 respondents. Data were collected using a questionnaire and analyzed through univariate and bivariate analyses using the Chi-square test. The results showed that the majority of respondents had good knowledge, adequate communication patterns, and most toddlers did not experience language development disorders. There was a significant relationship between parental knowledge and language development in toddlers (p-value = 0.041). Additionally, a significant relationship was found between parental communication patterns and language development in toddlers (p-value = 0.000). Parents are encouraged to increase their awareness of the importance of children's language development in order to support optimal growth and developmental outcomes.Keywords: Language Development, Toddler, Knowledge, Communication Pattern,  Parents